Inflow generation using Thomas- Fiering model for Thaphanseik Reservoir in Myanmar - Yin Nwe Latt; Win Win Zin; Zin Mar Lar Tin San (Researcher and Lecturer Society, 2024)
Thomas-Fiering (T-F) model was applied for generating synthetic streamflow for the Thaphanseik reservoir. The Thomas-Fiering model accommodated the non-stationarity of seasonal data. Time series of streamflow are crucial for the planning, design, and management of various water resource systems. In this study, the model was tested using historical data spanning 39 years (from 1985 to 2023). The model’s performance was evaluated by using statistical measurements such as Coefficient of Determination (R2) and Nash-Sutcliffe Efficiency (NSE). Additionally, this model was utilized to generate synthetic streamflow data for the years 2024 to 2100. The logarithmic transformation method was used in order to avoid the negative flows in the synthetic data. In this study, synthesis flow data were generated using different random sequences. The mean, standard deviation and correlation coefficient of different synthetic series were calculated. The calibration process was performed for the periods 1985 to 2016 and validation process was performed for the years 2017 to 2023. Based on R2 value, most suitable synthetic series were chosen. The generated data showed a high goodness of fit, with R² and NSE values. An analysis of the historical and synthetic discharge statistics revealed that the model successfully captured the features of the historical data and integrated them into the generated sequences.